Impact of COVID-19 on maternal and perinatal outcomes in Harare, Zimbabwe: a comparative maternal audit - Yemurai Bikwa; Grant Murewanhema; Mufaro Kanyangarara; Mugove G Madziyire; Zvavahera M Chirenje (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background The COVID-19 pandemic lockdown resulted in the disruption of health services in Zimbabwe. The objectives of this study were two-fold. First, the study sought to determine the impact of the lockdown on maternal and perinatal outcomes at two tertiary hospitals in Harare, Zimbabwe, using a maternal audit. Second, the study sought to estimate the potential effect of COVID-19 related decreases in coverage of maternal and newborn health interventions on maternal, and neonatal mortality in Zimbabwe using the Lives Saved Tool (LiST). # Methods A retrospective review of labour ward delivery registers, postnatal records and patients' maternity booklets was conducted. Data on total hospital deliveries, mode of delivery, and maternal and neonatal outcomes for March-August 2020 were abstracted and compared to data from March-August 2019. Logistic regression was performed to assess the association between maternal and perinatal outcomes and year as a proxy for the COVID-19 pandemic impact. Based on changes in coverage of interventions, LiST was used to estimate the impact of COVID-19 related disruptions on maternal and neonatal mortality at the national level. # Results A total of 19,835 hospital deliveries that occurred at Sally Mugabe and Mbuya Nehanda Maternity Hospitals (11,346 for 2019 and 8,489 for 2020) were reviewed. Compared to 2019, there was a significant increased likelihood of breech deliveries (odds ratio, OR=1.2; 95% confidenxce interval, CI=1.1-1.5), uterine ruptures (OR=2.3; 95% CI=1.1-5.1), stillbirths (OR=1.8; 95% CI=1.5-2.2) and neonatal deaths (OR=1.4; 95% CI=1.03-1.86) in 2020. However, there was a decrease in the odds of caesarean deliveries (OR=0.7; 95% CI=0.7-0.8). From the LiST analysis, if similar disruptions to maternity services were observed across the country for a 12 month period, there would be an excess of 343 maternal deaths, 2,658 neonatal deaths and 450 stillbirths nationally. # Conclusions These findings indicate a reduction in the utilisation of maternal health services and an increased risk of adverse maternal and neonatal outcomes during the nationwide lockdown. The provision of maternal and neonatal health services amid the pandemic remains crucial to reducing the negative indirect impacts of the pandemic.